Adoption of CRM Initiatives among the Small and Medium Enterprises- An Analysis - S, Sudhakar (Journal of Contemporary Research in Management (JCRM), 2015)
Smalland Medium enterprises (SMEs) in India are over 3 million in number producingover 8,000 items assume special significance for their role as a creator oflarge-scale employment opportunities apart from contributing considerably toregional development and industrial production (50 per cent), exports (42percent). The e-business technologies such as Customer Relationship Management(CRM) or Enterprise Resource Planning (ERP) are radical technologies that aretransforming business models and processes, resulting in the disruption of oldindustries and the creation of new ones. It is seen that firms that adopt radicaltechnologies tend to be more successful. The Indian SMEs must embracetechnology by upgrading in their business operations to sustain and enhance theircompetitiveness to face the onslaught of products from multinationalenterprises .The key to survival for many SMEs is the ability to exploit newtechnology such as CRM to improve productivity and cost efficiency, andgenerate new sales.Â Theresearch on CRM within the academic literature has primarily focused oninstallation issues such as gaining sponsor support, IT infrastructure, andtraining, rather than on factors that influence when, how, and why firmsâ€œadoptâ€ CRM and similar information technology. In India, the adoption of CRMis about 15% to 25% as per a few estimates made by CRM vendors. This researchwas carried out to fill a knowledge gap about CRM adoption among Indian SMEsegment which remains unexplored as most studies in Indian context exploresmostly service sectorÂ Herethe SMEs identified for the research belongs to manufacturing sector based inCoimbatore, India. Further study this is much different from other studieswhich concentrate on identification of adoption factors and developing aresearch model for adoption but here the researcher has identified theorganizational characteristics and how it influences the factors influencingthe adoption of CRM.Â SMEsis a crucial sector operating in hostile environments and facing increasingcompetition despite being the significant factor for job creation and economicgrowth are less studied by researchers regarding adoption of innovations. Thisresearch has thrown light on the adoption of innovations like CRM by IndianSMEs â€“ a relatively unexplored terrain.Â Themain objective identified in this study is to ascertain the critical factorsresponsible for adoption of CRM among Indian Small and Medium Enterprises(SMEs) based in Coimbatore which is an industrial city having a large number ofSMEs. The designed questionnaire has a five point Likert scales ranging fromstrongly agree to strongly disagree. The factors influencing the intention toadopt CRM technologies were technological factor, organizational factor,environmental factor, organizational readiness factor and perceived internal andexternal benefit factor. The researcher had used judgment sampling since theadopters of new technology among the SMEs were less in number.Â Thestudy adopted descriptive research and survey method. Based on the review ofliterature study on diffusion of innovation theories, two conceptual modelswere proposed and the hypotheses framed were tested using Structural EquationModeling (SEM).The statistical tools used in this study were Kolmogorovâ€“Smirnovtest (Kâ€“S test), Kruskal Wallis test, correlation, confirmatory factor analysisand structural equation modeling using Partial Least Squared (PLS) approach.The software used for conducting the analysis was SPSS version 16, Gpower 3.0.5Software and Visual PLS.Â Thisstudy found that relative advantage, complexity, observability, competitivepressure and government role had significant effects on the intention to adoptCRM among the SMEs based in Coimbatore. These findings do provide a significantview about the factors influencing the intention of adoption of CRM among theSMEs based in Coimbatore. Further the new knowledge obtained in this researchshall fuel more research in this area and also help Industry to understand CRMdevelopment. The results of this study shall be useful to SMEs, IT consultants,vendors of CRM and Government in drawing guidelines for encouraging CRMadoption and help Indian SMEs to compete better in the market.